Case Report: New Onset Lymphadenopathy After Immune Checkpoint Inhibitor Therapy Presents a Clinicopathological and Radiological Challenge - Scarlotta, Matthew; Avery, Robin; Baraban, Ezra; Maleki, Zahra; Ged, Yasser (Frontiers in Oncology, 2022)
The use of immune-checkpoint inhibitor (ICI) therapy has significantly improved patient outcomes in a wide variety of cancers and has become a cornerstone in the treatment of renal cell carcinoma. However, ICI treatment has the potential to cause a variety of immune-related adverse events (irAEs) that can affect any tissue or organ. This report describes the diagnostic dilemma of a patient with both RCC and diffuse large B-cell lymphoma who developed acute onset of fever and diffuse lymphadenopathy following treatment with combined ipilimumab and nivolumab. While diagnostic considerations included worsening lymphoma, hyperprogression of RCC, sarcoid-like reaction from immunotherapy, and fungal infection, his lymphadenopathy eventually resolved with treatment for histoplasmosis and discontinuation of immunotherapy. Despite only receiving two doses of immunotherapy, he has not required additional systemic therapy for RCC. This case demonstrates both the effectiveness of ICI therapy as well as the need for multidisciplinary approach to potential irAEs.